SURVEI LATAR BELAKANG WASIT SEPAKBOLA INDONESIA (STUDI PADA WASIT C-1 PENGCAB PSSI SIDOARJO JAWA TIMUR) - HANGGA PRADIGDA, DHANANG Hangga (Jurnal Prestasi Olahraga, 2013)
There are many important components in football which cannot be left, in order to make the competition running well. One of the important components is a referee. Referee is the leader of football. It means that a person who can make the competition be interested and fun is a referee. The problems of referee in every country are same, especially for Indonesian referee, they are: salary which is not always paid on time and safety for them when they have to lead a competition. While, the quality of the competition, especially football, it depends on the referee itself. If the prosperity and safety of the referee are ignored, it is not surprised, if the referee of the game cannot perform as well as a good referee for maximum standard. This research aims to describe background of referee C-1Sidoarjo Football Association of Indonesia. This background is about how the referees can get a license, their background of the study, their background of their jobs and their salaries. This research used descriptive qualitative research. The researcher got the data by directly interview with the referee of C-1 Sidoarjo Football Association of Indonesia. Then, the results of the data were listed and analyzed as well as possible. The results from the interview of C-1 Sidoarjo Football Association of Indonesia are from fifteen referees of C-1 Sidoarjo Football Association of Indonesia, there are five referees are their background of studies is an academician degree holder and for the others are graduates from Senior High School or on a level with. Then, referees of C-1 Sidoarjo Football Association of Indonesia, they do not only work as a referee in C-1 Sidoarjo Football Association of Indonesia, but also in another job. The results were obtained from the interviews is referee is not a main job, except as a referee they also have another job. So that, they do not rely on their salaries as a referee. Keywords : Referee of Football, Background, Sidoarjo Football Association of Indonesia